Mitochondrial DNA diversity of the long-tailed macaque (Macaca fascicularis) from the northern region of Peninsular Malaysia - Jeffrine J., Rovie-Ryan; Mohd Tajuddin, Abdullah; Frankie Thomas, Sitam; Soon Guan, Tan; Misliah M., Basir; Zaaba Zainol, Abidin; Charles, Keliang; Azroie, Denel (Department of Wildlife and National Parks, 2014)
We examined the genetic diversity of 64 long-tailed macaques from the northern states of Peninsular Malaysia covering the states of Perlis and Kedah including the Langkawi Island using the complete control region (CR) segment of the mitochondrial DNA. Standard genetic diversity including nucleotide diversity, haplotype diversity and genetic divergence were calculated. Moderate nucleotide diversity (π = 0.021) was observed which is higher than a previous study on the Penang M. fascicularis population. Twenty-three haplotypes were detected with haplotype diversity, h of 0.936. Haplotype sharing was observed among Langkawi and Perlis macaques indicating historical connection between the island and the mainland. Phylogenetic trees constructed grouped the samples into 4 groups without any obvious populations structuring.